Investigating Handwashing Frequency in Canadians as a Result of the COVID-19 Pandemic - Chen, Samuel; Heacock, Helen; BCIT School of Health Sciences, Environmental Health (BCIT Environmental Public Health Journal, 2021)
The COVID-19 pandemic was an unprecedented event that has generated many changes in public behaviour. The purpose of this study was to examine if Canadians are increasing their handwashing compliance due to the pandemic as well as to assess if different demographic variables are associated with handwashing knowledge or behaviour.